2020
DOI: 10.9734/jerr/2020/v13i417110
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Effects from Environmental Temperature on the Natural Frequencies of Cable-strut Structures

Abstract: The changes in dynamic properties such as natural frequencies and mode shapes are used in vibration health monitoring as tools for assessing the structures health status. They are, however, also affected by environmental conditions like wind, humidity and temperature changes. Of particular importance is the change of the environmental temperature, and it is the most commonly considered environmental variable that influences the vibration health monitoring algorithms. This paper discusses how cable-strut struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The changes in structural frequencies are produced due to the variation in the modulus of materials under varying temperatures. Through an optimization problem, Ashwear et al [18] studied the influence of changes in environmental temperatures on a cable-strut structure's dynamic properties. They found that the first natural frequencies are less susceptible to temperature variations.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in structural frequencies are produced due to the variation in the modulus of materials under varying temperatures. Through an optimization problem, Ashwear et al [18] studied the influence of changes in environmental temperatures on a cable-strut structure's dynamic properties. They found that the first natural frequencies are less susceptible to temperature variations.…”
Section: Introductionmentioning
confidence: 99%